2015
DOI: 10.1016/j.bbr.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Learning impairments identified early in life are predictive of future impairments associated with aging

Abstract: The Morris water maze (MWM) behavioral paradigm is commonly used to measure spatial learning and memory in rodents. It is widely accepted that performance in the MWM declines with age. However, young rats ubiquitously perform very well on established versions of the water maze, suggesting that more challenging tasks may be required to reveal subtle differences in young animals. Therefore, we have used a one-day water maze and novel object recognition to test whether more sensitive paradigms of memory in young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…Previous studies from our lab indicate that mild cognitive impairments can be found in rats as early as 3 months of age, and that these deficits early in life are predictive of cognitive deficits that develop with age (Hullinger & Burger, 2015). This suggests that behavioral intervention focused on improving cognition from an early time point could provide a buffer against age-related cognitive decline.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies from our lab indicate that mild cognitive impairments can be found in rats as early as 3 months of age, and that these deficits early in life are predictive of cognitive deficits that develop with age (Hullinger & Burger, 2015). This suggests that behavioral intervention focused on improving cognition from an early time point could provide a buffer against age-related cognitive decline.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies from our lab demonstrate that cognitive impairment can be identified in young rats using cognitively demanding versions of the Morris water maze and novel object recognition tasks, and that these impairments are predictive of cognitive impairments at 12 months of age (Hullinger & Burger, 2015). This suggests that interventions focused on improving cognition from an early age may provide a buffer against age related cognitive decline.…”
Section: Introductionmentioning
confidence: 98%
“…Previous longitudinal studies have indicated that behavioral/cognitive measures in young adults (Dellu et al, 1994;Dellu-Hagedorn et al, 2004;Talboom et al, 2014;Hullinger and Burger, 2015) or middle-age (Stone et al, 1997) may predict future learning and memory performance. We observed that the differential response to enter a novel environment at 6 months predicted impaired spatial memory in males at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Memory decline is the universal phenomenon in the aging process . The prolongation in escape latencies and shortening in target quadrant occupancy showed in aged rats in Morris Water Maze test are thought to reflect the age‐related impairments of learning and memory . Following Grifola frondosa polysaccharides administration, there was a significant improvement in learning and memory as evident from the decreasing escape latencies and increasing platform crossing times compared to the aged controls.…”
Section: Discussionmentioning
confidence: 99%